Monitoring and Quality Evaluation Method of English Teaching in Machine Manufacturing Based on Machine Learning and Internet of Things - Xie, Fang (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: With the continuous development of society, education is getting more and more attention, and all stages of education, such as elementary school, middle school, high school, Etc., are the fundamental objects of attention, while English in the university, as a critical foreign language, is also given considerable attention. Among the various majors in the university, different majors pay different attention to English, among which in the mechanical engineering major, the importance of English is still relatively front and centre, which is helpful for the improvement of students' mechanical engineering level. However, in the current teaching, there are still a series of problems in the English teaching of mechanical majors, which have certain obstacles to improving students' English level.OBJECTIVES: To give university English teachers more feedback and opinions through a reasonable and perfect teaching monitoring and quality evaluation method; combining their English reading teaching with relevant rules and regulations can better promote the educational quality level of university English and help students improve their English more reasonably.METHODS: To study and analyze the monitoring and quality evaluation of English teaching in mechanical majors to get the relevant optimization suggestions of teaching mode, and to solve the correlation problem based on multiple linear regression through the calculation of SPSS software, to analyze the final impact mechanism of each item on the quality of teaching.RESULTS: The results of the sample survey indicate that, firstly, five factors, namely, research direction, disciplinary ladder, scientific research, talent cultivation and management, will have a significant impact on the monitoring and quality evaluation of English teaching in the mechanical program. Secondly, further research on the influence mechanism suggests that the monitoring and quality evaluation of English language teaching in mechanical majors needs some improvement, affecting the English language proficiency of students in this field.CONCLUSION: After summarizing several factors that impact the evaluation of the quality of English teaching, it is clear that such English classroom teaching has a positive effect on the training of mechanical students.
Keywords: Machine learning and Internet of things; machine building; English teaching; monitoring and quality evaluation